A multicenter analysis on the changes of sIgE in China during the early period of COVID‐19 pandemic - Yunzhu Li; Linfeng Li (Immunity, Inflammation and Disease, 2023)
Abstract Objective This study aims to analyze the changes in allergen composition ratio during the early stages of the COVID‐19 outbreak in China and analyze the underlying factors contributing to these alterations. Methods A multicenter study approach was employed. A total of 618 male and female patients (0–89 years old) were recruited from the dermatology, pediatrics, and allergy departments of 17 hospitals across 15 Chinese cities between January 2020 and June 2021. Serum samples were collected and subjected to allergen‐specific immunoglobulin E (sIgE) detection using the reversed enzyme allegro‐sorbent test. The allergens included Dermatophagoides pteronyssinus (D. pteronyssinus), Dermatophagoides farina (D. farina), Ambrosia artemisiifolia (A. artemisiifolia), Salix babylonica (S. babylonica), dog dander, alternaria, cockroach, Artemisia argyi (A. argyi), cat dander, house dust, milk, hen's egg, mutton, cod, peanut, beef, soybean, shrimp, crab, and wheat. Each participant was required to exhibit at least one positive sIgE detection result (≥0.35 IU/mL). The chi‐square test was used to analyze the differences between groups. Results The positive sIgE proportion of inhalation allergens were significantly lower than that of ingestion allergens. As restrictions on outdoor activities and seafood imports persisted, the positive sIgE proportion of wheat and shrimp exhibited a significant decrease in the spring of 2021 compared to the corresponding period in 2020. Conversely, there was a substantial increase in the positive proportion of crab. The fluctuation in the ratio of D. pteronyssinus and D. farina appeared to be influenced more by seasonal factors rather than the COVID‐19 pandemic. However, no noteworthy disparities were observed in the proportions of other allergens. Conclusion The alterations in allergen composition during the initial phase of the epidemic may be attributed to several factors, such as decreased travel, increased mask usage, reduced carbohydrate consumption, and changes in seafood consumption. However, factors such as season, cultural practices, and customs may also influence the composition of allergens.